The potential role of roaming dogs in establishing a geographically novel life cycle of taeniids (Echinococcus spp. and Taenia spp.) in a non-endemic area - Mutwiri, Titus; Muigai, A.W.T.; Magambo, J.; Mulinge, E.; Gitau, L.; Muinde, Patrick; Bettridge, Judy M.; Rogan, M.; Fèvre, Eric M.; Falzon, Laura C. (Elsevier, 2023)
Introduction: Cystic Echinococcosis (CE) is endemic in humans and livestock in many pastoral communities in Kenya. The distribution of the disease is enhanced by several factors, including livestock trade, which has allowed for the spread of CE to non-endemic areas such as western Kenya. Dogs' roaming behaviour, with consequent contamination of the environment with intestinal parasites, could then lead to parasite establishment. This study examined dogs' infection levels with taeniid eggs and their potential role in contaminating the environment with intestinal parasites.